RELASI KUASA DALAM TAFSIR HAK DῙNI KUR’ĀN DILI : STUDI ATAS PENAFSIRAN ELMALILI HAMDI YAZIR TERHADAP AYAT POLIGAMI PADA MASA TRANSISI TURKI - Ardi Kurniawan; Darwis Hude; Nur Rofiah (El-Mu'Jam. Jurnal Kajian Al Qur'an dan Al-Hadis, 2026)
This article explores the relationship between power and Qur’anic interpretation by examining Elmalılı Hamdi Yazır’s exegesis of polygamy verses in the Turkish context. It argues that interpretation is not purely intellectual but often intersects with political authority, functioning as a tool of legitimacy for state policies. This dynamic became especially visible during Turkey’s transition from the Ottoman Caliphate to the modern Republic, when religious interpretation was mobilized to support emerging political ideologies and national identity. This study employs a qualitative library research method, drawing on primary sources from Elmalılı’s works and relevant secondary literature. Using descriptive-analytical and historical-critical-contextual approaches, the research situates his interpretation within broader socio-political transformations. The findings reveal that Elmalılı’s interpretation of polygamy reflects a high degree of intellectual independence and was not shaped by direct state intervention. He emphasizes justice as the central condition for polygamy, framing it within ethical, social, and humanitarian considerations. Rather than prohibiting the practice outright, he underscores that it must adhere to principles of fairness and public welfare. For Elmalılı, polygamy is not an unrestricted right but a conditional practice bound by moral responsibility and the historical context of revelation.